2013
DOI: 10.1108/bjom-jan-2012-0002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of national culture and ethno‐linguistic diversity on innovativeness

Abstract: PurposeThere is an established link between national cultural differences and documented variations in technological innovations across countries. To move beyond a narrow emphasis on national cultures, scholars have suggested using within‐country diversity to compensate for known limitations in national culture measures. Given that ethno‐linguistic diversity is a known source of cultural variation, this paper specifically aims to explore the relationship between culture, ethno‐linguistic diversity and national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 73 publications
2
19
0
Order By: Relevance
“…Prior research has focused on archival data to measure intra-cultural variation; works in political economy and international business have relied on ethnolinguistic diversity as a proxy to account for intra-cultural variation (e.g. Puia and Ofori-Dankwa, 2013). The use of ethnolinguistic diversity as an antecedent of intra-cultural variation has been well documented since Au's (1999) discussion of such concept.…”
Section: Independent Variable: Intra-cultural Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has focused on archival data to measure intra-cultural variation; works in political economy and international business have relied on ethnolinguistic diversity as a proxy to account for intra-cultural variation (e.g. Puia and Ofori-Dankwa, 2013). The use of ethnolinguistic diversity as an antecedent of intra-cultural variation has been well documented since Au's (1999) discussion of such concept.…”
Section: Independent Variable: Intra-cultural Variationmentioning
confidence: 99%
“…The fundamental tenet of intra-cultural variation is to show the extent to which the shared practices within a society are widely and deeply shared among its members (Puia and Ofori-Dankwa, 2013). Drawing on the multilayered construct of culture (Leung et al, 2005), Tung (2008) argued for the necessity to account for intra-national variation when conducting cross-cultural research.…”
Section: The Concept Of Intra-cultural Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Au and Cheung (2004) empirically demonstrated that intra-cultural variation and cultural mean are not substitutes, which provides supporting argument for the importance of studying the implications of both constructs. The fundamental importance of intra-cultural variation is to show the extent to which the shared practices within a society are widely and deeply shared amongst its members (Puia and Ofori-Dankwa, 2013). Drawing on the multi-layered construct of culture (Leung et al, 2005), Tung (2008a) argued for the necessity to account for intra-national variation when conducting cross-cultural research.…”
Section: Intra-cultural Variation Reviewmentioning
confidence: 99%
“…Others established a strong link between intra-country variation and technological innovations. Puia and Ofori-Dankwa (2013) employed the within-country diversity framework to explore the relationship between cultural diversity (within a given country) and national innovativeness. Their findings suggest that intra-cultural variation is independently and positively related to national innovativeness.…”
Section: Intra-cultural Variation Reviewmentioning
confidence: 99%